Ensino de geometria espacial : uma abordagem investigativa - Silva, Gilberlania Pereira Santos (2019)
The teaching of spatial geometry is most often seen as applying solids formulas and calculating surface areas, a process in which students play a passive role and the teacher assumes the role of content exhibitor. Believing that the teaching-learning process of geometry is more successful when the student assumes an active role, the spatial geometry content was worked in two classes of third year of high school using a mathematical research approach. To do so, based on the ideas of Ponte, Oliveira and Brocado (2009), the activities developed in fourteen days of classes were analyzed. In order to check the advantages and disadvantages of working with this active approach. With this, it was observed that several challenges are encountered by the teacher: better preparation and mastery of the content and methodologies to be used, greater time consumption for preparation and execution of the classes, a closer look at the difficulties of the students, between others. It was also observed that research allows the teacher to continually evaluate his students and to detect, in a more specific way, the individual difficulties of these students. In addition, it provides learners with a legitimate mathematical experience in which they construct mathematical knowledge while developing other skills such as working in groups and expressing themselves mathematically.